1987
DOI: 10.1161/01.hyp.10.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte ghost Na+,K+-ATPase and blood pressure.

Abstract: SUMMARY To examine the relationship between body mass index, blood pressure, and the Na + ,K + -adenosine triphosphatase (ATPase) system, we measured the erythrocyte ghost Na + ,K + -ATPase and the erythrocyte Na + concentration in 120 blacks and 127 whites (136 males and 111 females). Blacks showed a 13.9% higher erythrocyte Na + (7.63 ± 0.19 vs 6.70 ± 0.11 [SEM] mEq/L; p = 0.0001) and a 16.1% lower erythrocyte ghost Na + ,K + -ATPase activity (140.3 ± 4.2 vs 167.3 ± 4.7 nmol inorganic phosphate/mg protein/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This observation is consistent with diminished Na þ K þ -ATPase activity, which has been demonstrated in the red blood cells of African-Americans [5,[34][35][36] and might, therefore, play a role in producing a K þ deficient state.…”
Section: Discussionsupporting
confidence: 88%
“…This observation is consistent with diminished Na þ K þ -ATPase activity, which has been demonstrated in the red blood cells of African-Americans [5,[34][35][36] and might, therefore, play a role in producing a K þ deficient state.…”
Section: Discussionsupporting
confidence: 88%
“…In this context, while numerous investigators have reported that the activity of this enzyme is decreased in red blood cells in vitro of African Americans compared with Caucasian Americans [5,[36][37][38], no evidence of a racial difference in Na + ,K + -ATPase in skeletal muscle is currently available. Because skeletal muscle is by far the largest repository of K + and Na + ,K + -ATPase is the principal regulator of K + uptake by all cells, our observations in vivo may well indicate a more global reduction in activity of this enzyme in African Americans.…”
Section: Resultsmentioning
confidence: 99%
“…1217 " 20 A lower density of the Na + -K + pump cannot be a sole explanation for a rise in fibroblast Na + , as such a process will not be associated with increased Na + turnover rate. The present investigation suggests an additional and intriguing possibility: namely, increased passive Na + entry and, consequently, higher Na + extrusion through the Na + -K + pump in blacks.…”
Section: Discussionmentioning
confidence: 99%